Digital Tax Administration Reform and Tax Compliance in Transfer Pricing: - - Ely Kartikaningdyah; Putu Dian Pradnyanitasari (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Background: Global economic integration has driven the expansion of multinational corporations and increased the intensity of transactions between cross-border affiliates. In this context, transfer pricing has become a common mechanism for determining internal transaction prices. Although legal, this practice is often associated with profit shifting that can reduce the tax base in the country where the economic activity takes place, thus posing challenges for tax authorities, particularly in developing countries with limited oversight capacity and the complexity of cross-jurisdictional transactions. Purpose: This research seeks to examine how digital tax administration reforms, the integrity of tax consultants, tax socialization efforts, taxpayer awareness, and understanding of tax regulations influence the compliance of multinational corporations in transfer pricing, while also taking into account the moderating impact of tax sanctions. Method: The study usessan explanatory sequentialmmixed methods approach, combining qualitative and quantitative analysis. The qualitative stage was conducted through interviews with tax authorities, tax consultants, and corporate practitioners to validate the research constructs. The quantitative stage was conducted through a survey of 250 respondents from multinational companies in Indonesian industrial areas, analyzed using SEM-PLS. Result: The results show that taxpayer awareness and tax understanding have a positive and significant effect on taxpayer compliance with transfer pricing. In contrast, digital tax administration reform, tax consultant integrity, and tax socialization were insignificant. Tax sanctions were found to enhance the effect of taxpayer awareness and comprehension on compliance. Conclusion: The novelty of this research lies in the development of a tax compliance model that integrates digital administration reform, taxpayer behavioral factors, and law enforcement mechanisms. The findings indicate that taxpayer behavior and the effectiveness of sanctions play a more dominant role than administrative reform in encouraging tax compliance in the transfer pricing activities of multinational companies in developing countries.